Prostatic stromal sarcoma: A case report and literature review. Issue 18 (May 2018) - Yang, Weiping; Liu, Ailian; Wu, Jingjun; Niu, Miao
Abstract: Rationale: prostatic stromal sarcoma is a very rare malignant tumor that accounts for <0.1% of prostate malignancy. Patient concerns: we reported a 49-year-old man presented with dysuria and hematuria, whose computed tomography examination showed an enlarged prostate gland with an irregular shape. Diagnoses: the diagnosis was confirmed on the basis of imaging manifestations and histopathological findings which were proved as prostatic stromal sarcoma. Interventions: The patient underwent radical prostatectomy Outcomes: his postoperative condition was good. Abstract : Supplemental Digital Content is available in the text